A rare case of spontaneously dissolved calcification of the mitral annulus: Caseous calcification of the mitral annulus. Issue 3 (March 2018) - Takeuchi, Yasuyo; Motooka, Makoto; Sakamoto, Hiroki; Sakaguchi, Genichi; Watanabe, Hiroyuki; Shimada, Toshio
Abstract: Caseous calcification of the mitral annulus is a rare variant of mitral annular calcification (MAC). MAC is detected using conventional echocardiography and is prevalent in the elderly. However, limited information is currently available on the transformation of MAC. We herein report a case of a sudden liquified change in MAC, which was diagnosed using echocardiography and computed tomography. <Learning objective: The mechanisms underlying the pathogenesis of caseous calcification of the mitral annulus (CCMA) have not been elucidated in detail. This case report revealed the transition from mitral annular calcification to CCMA, indicating the marked transformation of calcification, which leads to spontaneous liquefaction.>